The Effect of Fixed Asset Intensity, Institusional Ownershop, and Company Size on Tax Avoidance in Textile and Garment Companies Listed on the Indoneisa Stock Exchange (IDX) in 2016-2021 - LUMANTO, Randy; WANGKAR, Anneke; TANGKUMAN, Steven (Journal of Governance, Taxation and Auditing, 2023)
This study examines the effect of Fixed Asset Intensity, Institutional Ownership, and Company Size on Tax Avoidance in Textile and Garment Companies Listed on the Indonesia Stock Exchange (IDX) in 2016-2021. This research uses secondary research. The sample in this study used a purposive sampling technique to obtain a selection of 5 companies which accumulated and got as many as 30 data. The analytical method used in this research is the multiple regression analysis method. The results of the study show that Fixed Asset Intensity has an effect on Tax Avoidance, Institutional Ownership has an impact on Tax Avoidance, and Company Size has no effect on Tax Avoidance.